Anatomy and Biomechanics of Scapulohumeral Rhythm – Concise Review - Mr. Vaithianathan Gnanasundaram; Dr. Hannah Sugirthabai Rajila Rajendran (Anatomy and Biomechanics of Scapulohumeral Rhythm – Concise Review, Edition 1, 2024)
The scapulohumeral rhythm is a complex biomechanical phenomenon involving a variety of skeletal muscle movements. Its importance in shoulder biomechanics research and clinical application has been well documented. This study seeks to offer a deeper comprehension of the complexities in shoulder mechanics, forming the groundwork for targeted treatments and rehabilitation methods aiming to enhance patient results. By integrating theoretical models with research data, the essay will provide a comprehensive view of the dynamic complexities of the rhythm within the scope of shoulder health and rehabilitation, emphasizing the crucial role of precise kinematic evaluations in identifying pathology and enhancing treatment approaches. The synthesis of these perspectives reveals the complex relationship between spherical and rotator cuff pathologies, stressing the critical necessity for precise assessment and specific interventions to address underlying muscle dysfunction and restore a healthy shoulder. In addition, a detailed understanding of the interplay between extrinsic conditions and musculoskeletal muscle functionality can be procured, thereby facilitating improved diagnostic precision and individualized therapeutic interventions aimed at reinstating normal shoulder function and function.